2019
DOI: 10.4236/jep.2019.105036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Instigating Land Use Conflicts in Selected Forest Reserves of Ondo State, Nigeria

Abstract: Practice of agriculture and other none forestry uses in forest reserves often generates conflict owing to the former's incompatibility with the latter. The need to identify the factors that triggers this conflict is germane to sustainable forest resources management. Thus, this paper report findings on various factors instigating land use conflicts in the high forest zone of Ondo state, Nigeria. Idanre and Oluwa forest reserves in the state were purposively selected for the study. Household counting was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…This further revealed a decline in forest resources owing to deforestation. This is in line with Aluko et al (2015) who reported that resources are reduced across gender line whenever disaster befalls any rural communities .This implies that the effect of deforestation has impacted negatively on the activities of NTFPs. In one of the focus group discussion, one of the participants reported thus:…”
Section: Difference In Perceived Effect Of Deforestation On Ntfps Activities Across Gendersupporting
confidence: 86%
“…This further revealed a decline in forest resources owing to deforestation. This is in line with Aluko et al (2015) who reported that resources are reduced across gender line whenever disaster befalls any rural communities .This implies that the effect of deforestation has impacted negatively on the activities of NTFPs. In one of the focus group discussion, one of the participants reported thus:…”
Section: Difference In Perceived Effect Of Deforestation On Ntfps Activities Across Gendersupporting
confidence: 86%